A New Pyrometallurgical Recycling Technique for Lead Battery Paste Without SO2 Generation—A Thermodynamic and Experimental Investigation - Yun Li (The Minerals, Metals and Materials Society)
An innovative lead recycling process from scrap lead-acid battery paste is presented. The novelty in the process is avoiding SO2 generation and emission by using reductive sulfur-fixing technique. Iron-bearing secondary wastes produced from metallurgical industry were utilized as sulfur-fixing agent to capture sulfur in the form of FeS (s) instead of generation of SO2 (g). Na2CO3 molten salt was added to the smelting system to speed the reactions and improve valuable metals’ recovery and sulfur-fixation efficiency. Furthermore, this process can simultaneously co-treat various lead and iron-bearing wastes. At the same time, some precious metals, such as Au and Ag, contained in iron-bearing wastes can be recovered. The feasibility and reliability of this process was investigated thermodynamically and experimentally with the help of HSC 9.0 database and XRD and SEM-EDS analysis. A possible reaction mechanism and path in PbSO4–Fe2O3–Na2CO3–C smelting system was also clarified.